Fair Distribution Heuristics for Parallel Processors - Otoom, Mohammad Mahmood (Communications in Mathematics and Applications, 2021)
This paper studies the machine covering problem to satisfy the fair distribution of several tasks with different execution times to be run on several parallel processors. My work deals with process scheduling on identical parallel processors and how to find the best solution to this problem. The goal is to maximize the finishing time for the processor with the least time regarding all other system processors. Some algorithms were proposed that can approximately solve the studied problem by minimizing the difference between the finishing time of all processors in the system.
Keywords: Heuristics; Fair distribution; Parallel processors; Process scheduling